Cardioprotective Effects of Ursodeoxycholic Acid in Isoprenaline-Induced Myocardial Injury in Rats - Dalibor Mihajlović; Đorđe Đukanović; Milica Gajić Bojić; Sanja Jovičić; Nebojša Mandić-Kovačević; Snežana Uletilović; Žana M. Maksimović; Nebojša Pavlović; Boris Dojčinović; Sergey Bolevich; Momir Mikov; Ranko Škrbić; et al. (Biomolecules, 2024)
Patients suffering from cholelithiasis have an increased risk of developing cardiovascular complications, particularly ischemic myocardial disease. Ursodeoxycholic acid (UDCA), already used in clinical practice for the treatment of cholelithiasis and related conditions, has proven antioxidative, anti-inflammatory, and cytoprotective effects. Therefore, the aim of this study was to investigate the cardioprotective effect of UDCA pre-treatment on isoprenaline-induced myocardial injury in rats. Male Wistar albino rats were randomized into four groups. Animals were pre-treated for 10 days with propylene glycol + saline on days 9 and 10 (control), 10 days with propylene glycol + isoprenaline on days 9 and 10 (I group), 10 days with UDCA + saline on days 9 and 10 (UDCA group), and 10 days with UDCA + isoprenaline on days 9 and 10 (UDCA + I group). UDCA pre-treatment significantly reduced values of high-sensitivity troponin I (hsTnI) and aspartate aminotransferase (AST) cardiac markers (p < 0.001 and p < 0.01, respectively). The value of thiobarbituric acid reactive substances (TBARS) was also decreased in the UDCA + I group compared to the I group (p < 0.001). UDCA also significantly increased glutathione (GSH) levels, while showing a tendency to increase levels of superoxide dismutase (SOD) and catalase (CAT). The level of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) expression, a key regulatory gene of inflammation, was diminished when UDCA was administered. A reduction of cardiac damage was also observed in the UDCA pre-treated group. In conclusion, UDCA pre-treatment showed a cardioprotective effect on isoprenaline-induced myocardial injury in rats, primarily by reducing oxidative stress and inflammation.